2009
DOI: 10.1056/nejmoa0808138
|View full text |Cite
|
Sign up to set email alerts
|

A New Diagnostic Test for Arrhythmogenic Right Ventricular Cardiomyopathy

Abstract: Routine immunohistochemical analysis of a conventional endomyocardial-biopsy sample appears to be a highly sensitive and specific diagnostic test for ARVC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
341
6
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 412 publications
(376 citation statements)
references
References 22 publications
26
341
6
3
Order By: Relevance
“…28 Finally, Asimaki et al showed that immunohistochemical analysis of conventional endomyocardial biopsy samples appears to be both a highly sensitive and specific diagnostic test for ARVC/D, as was demonstrated in a group of 11 ARVC/D patients. 26 Reduced immunoreactive signal levels of plakoglobin and Cx43 were found to be a consistent feature in patients with ARVC/D. Although we found reduced signal levels for plakoglobin in one of the p.Arg79X mutation carriers, this was not a consistent finding in another series of patients (data not shown) and further studies are required to establish the possible role of immunohistochemical analysis in patients with ARVC/D.…”
Section: B Amentioning
confidence: 51%
See 1 more Smart Citation
“…28 Finally, Asimaki et al showed that immunohistochemical analysis of conventional endomyocardial biopsy samples appears to be both a highly sensitive and specific diagnostic test for ARVC/D, as was demonstrated in a group of 11 ARVC/D patients. 26 Reduced immunoreactive signal levels of plakoglobin and Cx43 were found to be a consistent feature in patients with ARVC/D. Although we found reduced signal levels for plakoglobin in one of the p.Arg79X mutation carriers, this was not a consistent finding in another series of patients (data not shown) and further studies are required to establish the possible role of immunohistochemical analysis in patients with ARVC/D.…”
Section: B Amentioning
confidence: 51%
“…Immunohistochemical analysis of plakoglobin, based on the use of immuno peroxidase as described by Asimaki et al, 26 was performed on myocardial samples of patient III:1 from family G39. When compared with that of a myocardial sample of a control heart, a strong decrease of plakoglobin expression at the desmosomes, in both the right and left ventricle, was detected.…”
Section: Clinical Evaluation and Diagnostic Criteriamentioning
confidence: 99%
“…As expected, these mice develop cardiomyopathy with dilation, pronounced fibrosis and arrhythmia. It has been suggested that alterations in the ID localization of the plaque protein plakoglobin are reliable diagnostic criteria for ARVC, with important implications for its pathogenesis occurring in concert with the related arm-repeat proteins plakophilin 2 and β-catenin (Garcia- Gras et al 2006;Asimaki et al 2009;Fabritz et al 2011). We therefore examined the protein level and distribution of these polypeptides in our mouse model.…”
Section: A 38 -Endothelial Plasticity In Cardiac Valvesmentioning
confidence: 99%
“…5) It has recently been demonstrated that the expression of plakoglobin, a component of both the adherens junctions and desmosomes, was decreased in uninvolved myocardium of ARVC with normal expression of N-cadherin by immunostaining. 6) Moreover, the previous study showed that immunoreactive signals for connexin 43, a gap junction component, as well as plakoglobin, were also disturbed in around 70% of patients with ARVC. 7) However, no report has examined the relationships between these protein expressions and the clinical characteristics in ARVC.…”
mentioning
confidence: 99%